Hepatoprotective potential of Chrysin in a rat model of isoniazid- and rifampicin-induced hepatic injury: suppression of matrix metalloproteinase and transforming growth factor β - Deepa Mandlik; Akhilesh Tokey; Rohit Lokhande; Yash Dagadu; Heena Choudhary; Satish Mandlik (Future Journal of Pharmaceutical Sciences)
Abstract Background The ability of Chrysin (CHY) to scavenge free radicals has been widely explored. The scope of the research was to show that CHY protects the rat liver against damage caused by the drugs isoniazid (INH) and rifampicin (RFM). Results Rats were divided into 6 groups, each of which had six rats. Isoniazid (100 mg/kg, p.o.) and rifampicin (100 mg/kg, p.o.) were administered to Group II to VI rats for 21 days; this caused hepatocellular damage. CHY was administered in the dose of 50, 75, and 100 mg/kg, p.o. body weight to Group III to V rats before administration of INH + RFM. In this study, Group VI Silymarin (100 mg/kg, p.o.) functioned as the standard drug. The blood was drawn as the study was done, and tests for oxidative stress indicators, haematological parameters, biochemical parameters, and pro-inflammatory cytokines were performed. The liver samples were subjected to histopathology. The administration of CHY (50, 75, and 100 mg/kg) restored serum biochemical, haematological, proteins, and lipid parameters. Due to the administration of CHY, the levels of superoxide dismutase (SOD), glutathione oxidase (GSH), myeloperoxidase (MPO) and catalase (CAT) were also restored. The inflammatory cytokines such as tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9), transforming growth factor-β (TGF-β), malondialdehyde (MDA), myeloperoxidase (MPO) and nitric oxide (NO) levels were found to be decreased. The alterations in the biochemical parameters were reinforced by histological analysis of liver tissue. Conclusions It is concluded that the CHY protects against INH + RFM-induced oxidative liver injury in rats. Graphical abstract